2023
DOI: 10.1002/adfm.202215185
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Understanding of Active Sites of Non‐Noble Iron‐Nitrogen‐Carbon Catalysts for Oxygen Reduction Electrocatalysis

Abstract: Non-noble iron-nitrogen-carbon (Fe-N-C) catalysts have been explored as one type of the most promising alternatives of precious platinum (Pt) in catalyzing the oxygen reduction reaction (ORR). However, their catalytic ORR activity and stability still cannot meet the requirement of practical applications. Active sites in such catalysts are the key factors determining the catalytic performance. This review gives a critical overview on identification and understanding of active sties of non-pyrolytic and pyrolyti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(17 citation statements)
references
References 339 publications
(611 reference statements)
0
13
0
Order By: Relevance
“…It thus appears that both types of sites might be present in FeNC catalysts, but they may have different catalytic roles. Notably, different preparations yield FeNC catalyst materials with different impurities, side phases, and activities. , The preparation conditions might thus play a role in determining which active site motif is dominant, in terms of quantity and catalytic capability.…”
Section: Introductionmentioning
confidence: 99%
“…It thus appears that both types of sites might be present in FeNC catalysts, but they may have different catalytic roles. Notably, different preparations yield FeNC catalyst materials with different impurities, side phases, and activities. , The preparation conditions might thus play a role in determining which active site motif is dominant, in terms of quantity and catalytic capability.…”
Section: Introductionmentioning
confidence: 99%
“…Of note, recent research directions have revealed how M-N 4 sites' intrinsic activity can be modulated by incorporating heteroatoms, nanoclusters, and nanoparticles into the surrounding environment. [53][54][55] To date, while numerous reviews have summarized the noteworthy advancements in M-N-C SACs in lieu of precious metal-based electrocatalysts, 56,57 the systematic progress and the impact of associated particles on SACs ORR activity have been relatively scantily documented. 31,58 Therefore, this review exclusively focuses on the regulation in Fe-N 4 site surroundings within the Fe-N-C SACs, in view of establishing the structureactivity relationship that can influence the intrinsic activity (Figure 1C).…”
Section: Introductionmentioning
confidence: 99%
“…Under alkaline conditions, the cathode oxygen reduction reaction (ORR) are kinetically accelerated on a richer variety of catalysts that can be composed by nonprecious elements, and endowed with improved stabilities compared to the acid scenarios. [7][8][9][10] However, the anode hydrogen oxidation reaction (HOR) is severely repressed in alkaline conditions even by the state-ofthe-art Pt and/or its derived electrocatalysts, presenting ≈2 orders of magnitude lower activities than that in acidic media. [11] More fatally, these catalysts tend to be poisoned by trace CO in H 2 supply and deactivate rapidly.…”
Section: Introductionmentioning
confidence: 99%